(untitled) (Fiep Bulletin - online, 2013)
In this study, besides a theoretical and a legal approach of the issues that are being considered in teachers development and their constant reform at national level, highlighting the kind of professional profile to be developed by the universities in general (reflective and competent teachers), we tried to analyze the possibility of incorporating these concepts significantly by the professional-teachers of Physical Education, who are attending undergraduate or graduate programs. Therefore, from an open ended question, broken into two questions: “In your opinion, what makes a good teacher? What are the characteristics of a good teacher?”, we were able to observe the presence or not of characteristics that could lead to the development and consolidation of a reflective and/or competent teacher, considering which knowledge and/or competences would be seen as necessary to perform such social function. It was applied in three different contexts (in a study group, during the III CONPEF and in stricto sensu graduate programs), these questionings would allow us to contrast the discourses of different groups as we emphasize the backlashes of reflection and competent concepts as being fundamental to a good teacher.